The Independent Board of Commissioners and Institutional Ownership Structure on Earnings Management - Purbayasa, Sandi; Wiyanti, Rahma (Universitas Pamulang, 2024)
Financial reports are a source of information for internal and external parties regarding the condition and performance of a company. This information regarding the company's financial position, performance, and changes in the financial position of the company is beneficial for the company in making decisions. Profit is one of the essential elements in financial reports used to measure management performance. In this case, the profit and loss statement is the basis for assessing company performance, but high profits do not necessarily reflect ample cash; in this case, cash flow has more value in guaranteeing the company's performance in the future. In preparing financial reports, many frauds are committed by certain parties who only prioritize certain interests and are detrimental to stakeholders. Several studies show the possibility of intervention between management in carrying out the financial reporting process through decisions regarding company operations and estimates and accounting methods that will be used. Preparing financial reports involves management, the board of commissioners, and shareholders. Financial reports misused by management will affect the amount of profit shown. It is known as earnings management. The population in this research is all banking sector companies listed on the Indonesia Stock Exchange in 2017-2021, totaling 47 companies. Samples taken from the population must be truly representative. The sampling method used in this research used purposive sampling and descriptive statistical tests, and the research uses panel data regression analysis techniques. The results of the hypothesis research show that simultaneously, the independent board of commissioners and institutional ownership structure affect earnings management, while partially, the independent board of commissioners and institutional ownership structure hurt management in banking companies listed on the Indonesia Stock Exchange for the 2017 - 2021 period.